Digitaler Euro: Funktionsweise und kritische Würdigung; The digital euro: Functionality and critical appraisal - Friedrich Thießen (Wirtschaftsdienst, 2021)
Im Oktober 2020 veröffentlichte die EZB das Grundlagenpapier zum digitalen Euro. Es enthält Vorschläge für die Konstruktion der neuen Geldform. Das digitale Geld wird in zwei Formen vorkommen: einer Kontoform und einer Form als Inhaberinstrument. Im Frühjahr 2021 führte die EZB eine Befragung bei Privatpersonen und Unternehmen zu diesen Vorschlägen durch, deren Ergebnisse im April 2021 veröffentlicht wurden. Die Konstruktionsvorschläge des digitalen Geldes entspechen noch nicht in allen Punkten den gewünschten Funktionalitäten sowie den Aktivitäten von Wettbewerbssystemen. – – In October 2020, the ECB published the foundational paper on the digital euro. In spring 2021, it surveyed individuals and companies on these proposals, the results of which were published in April 2021. This paper compares the design proposals with the survey results as well as the activities of competitive systems. It shows that important aspects remain unresolved. The survey showed that global payment capability is an urgent desire. Easy-to-use 'onboarding' without IBAN is also expected. Another goal should be the independence of European payments from third-party intervention, as was the case in the Iran-U.S. conflict. A reform of the correspondent banking network via SWIFT with a centralisation of balance settlement could possibly deliver results as good as those of the ECB's digital money.
Keywords: E42; E50; 330; Euro; Digitalisierung; EU-Staaten